Modelling habitat suitability of sugar palm (Arenga pinnata) in Andongrejo Resort, Meru Betiri National Park, East Java, Indonesia - AGUS HIKMAT; ERVIZAL A. M. ZUHUD; EDHI SANDRA; PRIMADHIKA AL MANAR; FRISCHA DHELA WANNA PUTRI; HEKMATYAR AULIA AYUBA (Society for Indonesian Biodiversity, 2025)
Abstract. Hikmat A, Zuhud EAM, Sandra E, Al Manar P, Putri FDW, Ayuba HA. 2025. Modelling habitat suitability of sugar palm (Arenga pinnata) in Andongrejo Resort, Meru Betiri National Park, East Java, Indonesia. Biodiversitas 26: 4077-4089. Sugar palm (Arenga pinnata) is a species of the Arecaceae family with considerable economic, social, and ecological importance. This study aimed to model the habitat suitability of sugar palm and generate a suitability map based on the relationship between known presence points and key environmental variables. Using Maximum Entropy (MaxEnt) modelling, habitat suitability was predicted and classified based on the relationship between known occurrences and environmental variables. Seven environmental variables were found to contribute to the habitat suitability model. Among them, temperature (49.5%), altitude (29%), and distance from the river (7.7%) were identified as the most influential. The model achieved a high level of accuracy, with an Area Under the Curve (AUC) value of 0.942, indicating excellent predictive performance. Habitat suitability in the Andongrejo Resort, Meru Betiri National Park, East Java, Indonesia, was categorized into five classes: not suitable (11.17 ha), less suitable (4,882.56 ha), quite suitable (144.28 ha), suitable (42.96 ha), and very suitable (33.64 ha). The findings show that highly suitable habitats occupy a much smaller area compared to less suitable ones, which could threaten the long-term survival of sugar palm populations in the region. Notably, areas with high habitat suitability were mainly found within the forest zone, covering approximately 29.24 ha. These findings provide spatial guidance for habitat management, including restoration and conservation planning, particularly in the forest zones where suitable habitats are concentrated.